Methodological features of constructing the training process of basketball in physical education clubs in general education schools. - Uteuliev Mukhtar Uteulivich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article examines the issues of planning and improving the pre-competition training of young basketball players and the comprehensive system, features, and structure of training young basketball players.